2000
DOI: 10.1053/rmed.1999.0750
|View full text |Cite
|
Sign up to set email alerts
|

Untreated idiopathic aneurysm of the pulmonary artery; long-term follow-up

Abstract: A 57-year-old man with an idiopathic aneurysm of the left pulmonary artery is presented. The aneurysm was stable over many decades. No such long-term follow-up of an idiopathic pulmonary aneurysm has been described previously. After 39 years there is no evidence of heart failure or pulmonary hypertension. Because corrective surgery has a variable outcome, and prognosis is suggested to be good in the idiopathic form of pulmonary aneurysm, no surgical correction was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 6 publications
0
20
0
4
Order By: Relevance
“…A case report suggested that the long-term outcome of pulmonary artery aneurysm was favorable without surgical treatment. 4 It is unclear whether there is a size hinge point similar to aortic aneurysms in which the risk of complication increases. Although some recommend medical treatment for such patients, 4 others recommend surgical intervention for those with an aneurysm that has a diameter of 60 mm or greater.…”
mentioning
confidence: 99%
“…A case report suggested that the long-term outcome of pulmonary artery aneurysm was favorable without surgical treatment. 4 It is unclear whether there is a size hinge point similar to aortic aneurysms in which the risk of complication increases. Although some recommend medical treatment for such patients, 4 others recommend surgical intervention for those with an aneurysm that has a diameter of 60 mm or greater.…”
mentioning
confidence: 99%
“…On the other hand, conservative treatment is advocated when there is no left-to-right cardiac shunt or significant pulmonary hypertension [6]. …”
Section: Discussionmentioning
confidence: 99%
“…7 The pathological criteria for idiopathic aneurysm are described as, (1) Dilation of pulmonary trunk (involvement of arterial tree might or might not be present), (2) Absence of extra-or intra-cardiac shunts, (3) Absence of pulmonary disease or chronic cardiac disease, and (4) More than minimal atheromatosis or pulmonary vascular tree arteriosclerosis or absence of arterial disease. 8 According to these criteria, the patient had idiopathic pulmonary artery aneurysm. PAAs can be classified into proximal (or central) PAAs and peripheral PAAs.…”
Section: Discussionmentioning
confidence: 99%